Money, Currency and Crisis
1 online resource
Keywords: "Money is a core feature in all discussions of economic crisis, as is clear from the debates about the responses of the European Central Bank and the Federal Reserve Bank of the United States to the 2008 economic crisis.This volume explores the role of money in economic performance, and focuses on how monetary systems have affected economic crises for the last 4,000 years. Recent events have confirmed that money is only a useful tool in economic exchange if it is trusted, and this is a concept that this text explores in depth. The international panel of experts assembled here offers a long-range perspective, from ancient Assyria to modern societies in Europe, China and the US.This book will be of interest to students and researchers of economic history, and to anyone who seeks to understand the economic crises of recent decades, and place them in a wider historical context."--Provided by publisher.